THE TYPES OF COMMUNICATION STRATEGIES USED BY SPEAKING CLASS STUDENTS WITH DIFFERENT COMMUNICATION APPREHENSION LEVELS IN ENGLISH DEPARTMENT OF PETRA CHRISTIAN UNIVERSITY, SURABAYA - I. Tiono, Nani; Sylvia, Agatha (k@ta: A Biannual Publication on the Study of Language and Literature, 2005)
This article reports on a study that aims to find out the types of Communication Strategies used and mostly used by students with high and low levels of Communication Apprehension and whether students with high level of Communication Apprehension used more numbers of Communication Strategies. The subjects in a created classroom were asked to retell a pictorial story and a pictorial instruction. The results showed that students with high Communication Apprehension level used more numbers of Communication Strategies.